2014
DOI: 10.1080/09589236.2014.931801
|View full text |Cite
|
Sign up to set email alerts
|

Whatever happened to the F word in higher education?

Abstract: Abstract:As a women's studies academic who has taught health and social care students for four years in the UK, it strikes me that much of what and how I teach is incompatible with my own pedagogic position. At a time of government cuts and economic austerity there are ever shrinking opportunities to work in women's studies environments within the higher education academy, and I often find there is a mismatch between what I am offering as an academic and what an employer is looking for. Occupying the most juni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Hall (2016) suggests that the expansion of education may not always reduce the unemployment risk. One needs to be aware of the possible mismatch which may appear between academic teaching and job market requirements (Wright, 2014). Despite this, the study's results did not confirm it, and the authors found in line with Zimmer (2016) that less educated people of both genders face a greater risk of being unemployed (Jurajda and Terrell, 2009).…”
Section: Research Findings and Discussionmentioning
confidence: 77%
“…Hall (2016) suggests that the expansion of education may not always reduce the unemployment risk. One needs to be aware of the possible mismatch which may appear between academic teaching and job market requirements (Wright, 2014). Despite this, the study's results did not confirm it, and the authors found in line with Zimmer (2016) that less educated people of both genders face a greater risk of being unemployed (Jurajda and Terrell, 2009).…”
Section: Research Findings and Discussionmentioning
confidence: 77%
“…Feminist academics in the US face what has been called a 'Chilly Climate' (Chilly Collective, 1995;Dixon, 2013), perhaps struggling to find research and paedagogical space within the Academy (Wright, 2014). The UK context provides particular concerns for academics, including the move towards managerialism.…”
Section: Feminist Academicsmentioning
confidence: 97%
“…Substantively, women are less likely to be cited (Ferber, 1988; Maliniak et al, 2013) or invited to speak at conferences or be on panels (Yong, 2017); more likely to have their work devalued (Jenkins, 2014; Wright, 2014) or ranked lower than their male counterparts in peer review processes when author identities are known (Le Goues et al, 2018). Women are more likely to be viewed as ‘teachers’ rather than ‘researchers’, and undertake far more of the administrative obligations than their male counterparts (Misra et al, 2011).…”
Section: Gender and The Higher Education Contextmentioning
confidence: 99%